(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Observations on the ethology and types of damages to stored food-products caused by Pyralis farinalis (L.) are reported. It has been proved, by means of laboratory observations on breedings, that the larvae are able to survive and fullfill their biological life cicle only on foods that are partially mold-grown, whereas their development is blocked at an early life stage when foods are not contamined by fungus mycelium. Their fungus diet has been defined by analyzing the substances contained in the intestine of larvae living on an infested media, which are rich of microfungi, bacteria, and yeasts. The P. farinalis has a variable reproductive behaviour, depending on its habitat, the type of food available and the microclimate in which it lives therefore it has, according to these parameters, one or two generations annually; in particularly unfavorable conditions, its reptoductive activity gets slowed down considerably, consequently the breeding rate is limited to one generation every two years.